Evaluation of Educational Programs in Improving the Quality of Learning at MTs Al Halim Ledong Barat Private School - Ritonga, Syahrial (Indonesian Journal Education, 2023)
This study aims to find out how the evaluation of educational programs in improving the quality of learning in MTsS. Al Halim Ledong Barat. The research method used in this study is a qualitative research method in which researchers obtain information from interviews and documentation as well as observations at MTsS. Al Halim in Ledong Barat. The results of the research regarding the evaluation of the education program at this school are quite good because each evaluation of the teachers will know where their weaknesses are and learn to improve better and provide good teaching to students in order to get a better quality of learning